2019
DOI: 10.18268/bsgm2019v71n2a2
|View full text |Cite
|
Sign up to set email alerts
|

Technology and local wisdom: The Maya soil classification app

Abstract: El conocimiento maya sobre los suelos ha superado la desconfianza de los edafólogos hacia el conocimiento indígena puesto que es un sistema de clasificación con conceptos organizados jerárquicamente. Con el propósito de difundir y mejorar el conocimiento tradicional, desarrollamos la app clasificación maya de suelos. Esta app incluye tanto la descripción del suelo maya, como de tres de sus términos ecológicos (Petén, Kankabal y A'kalche) que vinculan el medio ambiente físico y biótico. La app incluye fotografí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The main soils used in Yucatan Peninsula are: K'ankab lu'um (red soil) and Box lu'um (black soil) [20]. This classification comes from the Mayan language, and is widely used in the Yucatan Peninsula (southeast region in Mexico) to refer to soils of different colors [21]. The work previously conducted by Oney-Montalvo et al [22] reported that the red soils have the highest concentration of calcium (2075.28 ± 29.70 mg kg −1 ), magnesium (779.23 ± 12.71 mg kg −1 ), phosphorus (11.00 ± 2.38 mg kg −1 ), iron (6.27 ± 0.21 mg kg −1 ) and the lowest concentration of organic matter (5.16 ± 0.04%).…”
Section: Introductionmentioning
confidence: 99%
“…The main soils used in Yucatan Peninsula are: K'ankab lu'um (red soil) and Box lu'um (black soil) [20]. This classification comes from the Mayan language, and is widely used in the Yucatan Peninsula (southeast region in Mexico) to refer to soils of different colors [21]. The work previously conducted by Oney-Montalvo et al [22] reported that the red soils have the highest concentration of calcium (2075.28 ± 29.70 mg kg −1 ), magnesium (779.23 ± 12.71 mg kg −1 ), phosphorus (11.00 ± 2.38 mg kg −1 ), iron (6.27 ± 0.21 mg kg −1 ) and the lowest concentration of organic matter (5.16 ± 0.04%).…”
Section: Introductionmentioning
confidence: 99%